Cyberslacking and psychological distress in school-going adolescents and its impact on their mothers’ mental health - P. C. Pradeep Kumar; Sithara M. Chako; Shivanand Manohar; M. Kishor (Archives of Mental Health)
Background: Smartphone use has significantly increased among adolescents for nonacademic purposes. The study aimed to assess cyberslacking and psychological distress among male and female school-going adolescents and its effects on mothers’ mental health. Methods: This cross-sectional study involved 532 school-going adolescents and their mothers through purposive sampling. A sociodemographic data sheet, academic cyberslacking scale, K10 psychological distress scale, and general health questionnaire were used to collect data from adolescents and mothers. Results: The study showed that accessing online content and sharing are the most common online activities among participants, at 61.84% and 44.55%, respectively. The mean score of domains of cyberslacking, including sharing (P = 0.001), shopping (P = 0.001), real-time updating (P = 0.001), accessing online content (P = 0.001), and gaming (P = 0.001), were significantly higher among male adolescents than female. In contrast, psychological distress was slightly higher among female adolescents. Concerning mothers’ mental health, adolescents’ psychological distress was positively associated with mothers’ somatic symptoms (r = 0.117*, P = 0.007), anxiety (r = 0.183*, P = 0.005), and depression (r = 0.102*, P = 0.018). Shopping (r = 0.113*, P = 0.003) and updating content on social media (r = 0.185*, P = 0.005) also increased depression in mothers. Logistic regression exhibited that age (P = 0.011, odds ratio [OR]: 1.346), online gaming (P = 0.001, OR: 0.890), and shopping in adolescents (P = 0.001, OR: 0.946) predicted somatic symptoms, anxiety, and depression in mothers. Conclusion: Cyberslacking is associated with increased psychological distress and depression. Cyberslacking in adolescents correlated with depression, anxiety, and somatic symptoms in mother.